Mechatronic Feasibility of Minimally Invasive, Atraumatic Cochleostomy. (6th July 2014) - Williamson, Tom; Du, Xinli; Bell, Brett; Coulson, Chris; Caversaccio, Marco; Proops, David; Brett, Peter; Weber, Stefan
Abstract : Robotic assistance in the context of lateral skull base surgery, particularly during cochlear implantation procedures, has been the subject of considerable research over the last decade. The use of robotics during these procedures has the potential to provide significant benefits to the patient by reducing invasiveness when gaining access to the cochlea, as well as reducing intracochlear trauma when performing a cochleostomy. Presented herein is preliminary work on the combination of two robotic systems for reducing invasiveness and trauma in cochlear implantation procedures. A robotic system for minimally invasive inner ear access was combined with a smart drilling tool for robust and safe cochleostomy; evaluation was completed on a single human cadaver specimen. Access to the middle ear was successfully achieved through the facial recess without damage to surrounding anatomical structures; cochleostomy was completed at the planned position with the endosteum remaining intact after drilling as confirmed by microscope evaluation.